Comprehensive study of secondary metabolite profile and pharmacological effects of medicinal plant Toddalia asiatica - Sathyamoorthy Jhansi Lakshmi, Upendra Raje Siddiraju (Journal of Applied Pharmaceutical Science, 2022)
Toddalia asiatica (L) Lam is a liana commonly known as an orange climber and is a monotypic genus belonging to the family “Rutaceae.” It is one of the widely distributed medicinal plants in the countries, i.e., South Africa, north tropical regions of Africa, Asia, and also in Madagascar. Compounds that exhibit various pharmacological effects, isolated from the various parts of the plant Toddalia asiatica, such as root, root bark, stem, stem bark, flowers, fruits, and leaves have been of prime importance. Traditional medicinal practitioners of the Asian continent have been using this plant since ancient times to treat ailments such as pulmonary diseases and inflammation of joints known as rheumatism. The root and the root bark of the plant are said to be more potent and are used as a remedy for the conditions such as fever, malaria, cholera, diarrhea, neuralgia, sprains, and epilepsy. Fruits of the plant are used as a medication in the conditions, i.e., cough, digestive abnormalities, and viral influenza infection. The vital oil obtained from the root bark of the plant T. asiatica is known to produce strong larvicidal activity against the mosquito species Aedes. The present review emphasizes a variety of pharmacologically active secondary metabolites extracted from the medicinal plant T. asiatica such as coumarins, toddaculin, toddalactone, and their pharmacological effects such as in antiinflammatory, bactericidal, fungicidal, antimalarial, antidiabetic, antiviral, and antitumor activity
Keywords: Toddalia asiatica, traditional medicine, root bark, coumarins, antimalarial activity, antimicrobial activity, antitumor activity